2018
DOI: 10.1021/acs.jafc.8b06392
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Profile in Manzanilla Table Olives As Affected by Water Deficit during Specific Phenological Stages and Spanish-Style Processing

Abstract: Reducing water consumption on agriculture is a worldwide goal toward sustainability. In this scenario, two experiments of regulated deficit irrigation (RDI) were carried out on olive trees, cultivar Manzanilla. With regard to experiment A, three RDI techniques were applied during the olive pit hardening period (stage II), while in experiment B, two RDI treatments were applied during the rehydration phase (stage III). Table olives under RDI are so-called hydroSOStainable. The effect of water deficit and Spanish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…A high proportion of table olive polyphenols are very susceptible to chemical degradation when they are submitted to the acidic conditions of digestion [15]. It was formerly described the polyphenolic profile of hydroSOStainable table olives of the current research [3], and it was found an increase of oleuropein, comselogoside, and verbascoside on A1 treatment as compared with control, as well as an increase of elenoic acid glucoside, oleuropein, and comselogoside regarding RDI treatments of experiment B. Beside this increases, it was previously reported that only 25% of oleuropein (one of the most important polyphenols in table olives) was stable during digestion, as well as only 20% of comselogoside and elenoic acid derivatives [15]. Flavonoids, verbascoside, and hydroxytyrosol derivatives also presented a small TPC bioaccessibility in a research conducted with three table olives cultivars [14].…”
Section: Antioxidant Activity and Total Phenolic Contentmentioning
confidence: 99%
See 3 more Smart Citations
“…A high proportion of table olive polyphenols are very susceptible to chemical degradation when they are submitted to the acidic conditions of digestion [15]. It was formerly described the polyphenolic profile of hydroSOStainable table olives of the current research [3], and it was found an increase of oleuropein, comselogoside, and verbascoside on A1 treatment as compared with control, as well as an increase of elenoic acid glucoside, oleuropein, and comselogoside regarding RDI treatments of experiment B. Beside this increases, it was previously reported that only 25% of oleuropein (one of the most important polyphenols in table olives) was stable during digestion, as well as only 20% of comselogoside and elenoic acid derivatives [15]. Flavonoids, verbascoside, and hydroxytyrosol derivatives also presented a small TPC bioaccessibility in a research conducted with three table olives cultivars [14].…”
Section: Antioxidant Activity and Total Phenolic Contentmentioning
confidence: 99%
“…Field characteristics of both experiments could be found in the work by Sánchez-Rodríguez and Cano-Lamadrid et al [3]. Climatic conditions could be considered equal for both experiments because only 10 km separated the farms.…”
Section: Experiments Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that olives grown under moderate irrigation stress had the highest content of PUFA, and in particular, linoleic acid. The same research group [24] carried out a study by applying a similar irrigation experimental plan and evaluated its influence on the phenolic profile of Spanish style Manzanilla olives. Results evidenced that a moderate level of irrigation increased the amounts of some polyphenols in table olives, especially those of compounds with health promoting activities, such oleuropein and oleoside diglucoside.…”
Section: Treated Green Olives or "Spanish Style"mentioning
confidence: 99%